Effectiveness Extending Concept Through Language Activities (ECOLA) Method in Learning Editing Student Scientific Articles - Asep Supriyana; Emzir E; Endry Boeriswati (Indonesian Language and Literature Education Study Program and LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2019)
This study aims to determine the effectiveness of the ECOLA method on the ability to edit scientific articles of students. The method used in this research is the expriment method. This method is used to examine the possibility of a causal relationship, by exposing one or more experimental groups and one or more experimental conditions. The design used in this study is the pretest posttest control group design. This research was conducted at the Indonesian Literature Study Program, Faculty of Language and Art, Jakarta State University. In this study, the independent variable is the ECOLA learning method and the dependent variable is the ability to edit scientific articles. Based on the research results it is known that there is an effective ECOLA method used to improve the ability to edit scientific articles of students. Keywords: ECOLA methods, editing skills, scientific articles Abstrak Penelitian ini bertujuan untuk mengetahui efektivitas metode ECOLA terhadap kemampuan menyunting artikel ilmiah mahasiswa. Metode yang digunakan dalam penelitian ini adalah metode exprimen. Metode ini digunakan untuk meneliti kemungkinan hubungan sebab akibat, dengan cara mengekspos satu atau lebih kelompok eksperimental dan satu atau lebih kondisi ekperimen. Desain yang digunakan dalam penelitian ini adalah pretest posttest control group design. Penelitian ini dilaksanakan di Program Studi Sastra Indonesia, Fakultas Bahasa dan Seni, Universitas Negeri Jakarta. Dalam penelitian ini, variabel bebas berupa metode pembelajaran ECOLA dan variabel terikatnya adalah kemampuan menyunting artikel ilmiah. Berdasarkan hasil penelitian diketahui terdapat metode ECOLA efektif digunakanuntukl meningkatkan kemampuan menyunting artikel ilmiah mahasiswa. Kata kunci: metode ECOLA, kemampuan menyunting, artikel ilmiah